The slow road from serfdom: Labor coercion and long-run development in the former Russian Empire - Johannes C. Buggle; Steven Nafziger (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper examines the long-run economic consequences of Russian serfdom. Employing data on the intensity of labor coercion at the district level in just prior to emancipation in 1861, we document that a greater legacy of serfdom is associated with lower economic well-being today. Our estimates imply that increasing historical serfdom by 25 percentage points reduces household expenditure today by up to 17%. The analysis of different types of labor coercion reveals substantial heterogeneity in the long-run effects of serfdom. Furthermore, we document persistence of economic development measured by city populations over the period 1800 - 2002 in cross-sectional regressions and panel estimations. Exploring mechanisms, our results suggest that the effect of serfdom on urbanization in Imperial Russia was perpetuated in the Soviet period, with negative implications for structural change, the spatial distribution and productivity of firms, and human capital investment.
URN:NBN:fi:bof-201812182156
Keywords: N33; N54; O10; O43; 330